2020
DOI: 10.1080/13504851.2020.1808165
|View full text |Cite
|
Sign up to set email alerts
|

Financialization, digital technology and income inequality

Abstract: This paper investigates the impact of digital technology on the relationship between financialization and income inequality of 54 countries from 2010 to 2015. The results show that financialization and digital technology widen the income inequality gap. Therefore, policies should be centred primarily on eliminating obstacles and developing innovative products that focus on solutions to the low-income consumer problem and those who have been marginalized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 22 publications
0
11
0
1
Order By: Relevance
“…There are few studies on the relationship between digitalization and income inequality. However, some studies report that progress in digital technology decreases income inequality (Richmond and Triplett, 2018;Canh et al, 2020), while some note that digitalization increases it (M€ onnig et al, 2019;Law et al, 2020;Mohd Daud et al, 2020).…”
Section: The Effect Of Digitalization On Income Inequalitymentioning
confidence: 99%
“…There are few studies on the relationship between digitalization and income inequality. However, some studies report that progress in digital technology decreases income inequality (Richmond and Triplett, 2018;Canh et al, 2020), while some note that digitalization increases it (M€ onnig et al, 2019;Law et al, 2020;Mohd Daud et al, 2020).…”
Section: The Effect Of Digitalization On Income Inequalitymentioning
confidence: 99%
“…The results suggest that digitalization alleviates income inequality [ 38 ]. Others believe that digitalization could exacerbate income inequality [ 39 , 40 ]. By applying a generalized linear mixed model and a random effects model based on Australian household panel data covering 2011–2017, Ali et al (2019) found that gross information and communication technology affordability is positively associated with income distribution and socioeconomic inequality [ 41 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The digital divide influences a wide range of economic, social and personal life spheres as well, from social to financial (Mohd Daud et al 2021 ), labour market (Al Mamun and Wickremasinghe 2014 ) and relations with institutions, particularly government (Robinson et al 2022 ). The issues targeted by digital divide studies are usually related to the internet.…”
Section: The Gender Gap Digital Divide and The Labour Marketmentioning
confidence: 99%